Genetic variation in the nuclear factor κB pathway in relation to susceptibility to rheumatoid arthritis. Issue 4 (23rd April 2008) - Dieguez-Gonzalez, R; Akar, S; Calaza, M; Perez-Pampin, E; Costas, J; Torres, M; Vicario, J L; Velloso, M L; Navarro, F; Narvaez, J; Joven, B; Herrero-Beaumont, G; et al.
Abstract : Objective: To examine genetic association between rheumatoid arthritis (RA) and known polymorphisms in core genes of the nuclear factor (NF)κB pathway, the major intracellular pathway in RA pathogenesis. Methods: Discovery and replication sample sets of Spanish patients with RA and controls were studied. A total of 181 single nucleotide polymorphisms (SNPs) uniformly spaced along the genomic sequences of 17 core genes of the NFκB pathway (REL, RELA, RELB, NFKB1, NFKB2, NFKBIA, NFKBIB, NFKBIE, IKBKA, IKBKB, IKBKE, IKBKAP, KBRAS1, KBRAS2, MAP3K1, MAP3K14, TAX1BP1) were studied by mass spectrometry analysis complemented with 5′-nuclease fluorescence assays in the discovery set, 458 patients with RA and 657 controls. SNPs showing nominal significant differences were further investigated in the replication set of 1189 patients with RA and 1092 controls. Results: No clear reproducible association was found, although 12 SNPs in IKBKB, IKBKE and REL genes showed significant association in the discovery set. Interestingly, two of the SNPs in the IKBKE gene, weakly associated in the discovery phase, showed a trend to significant association in the replication phase. Pooling both sample sets together, the association with these two SNPs was significant. Conclusion: We did not find any major effect among the explored members of the NFκB pathway in RA susceptibility. However, it is possible that variation in the IKBKE gene could have a small effect that requires replication in additional studies.